Chemical Properties of a Polysaccharide Purified From Solid‐State Fermentation of Auricularia Auricular and its Biological Activity as a Hypolipidemic Agent. Issue 9 (1st August 2013) - Zeng, Feng; Zhao, Chao; Pang, Jie; Lin, Zhanxi; Huang, Yifan; Liu, Bin
Abstract: A water‐soluble crude polysaccharide was extracted by hot water from Auricularia auricular mycelium grown under solid‐state fermentation (SSF). The crude polysaccharide was purified by DEAE Sephadex A‐50 and Sephadex G‐200 chromatography. Fourier transform infrared spectroscopy and nuclear magnetic resonance ( 1 H NMR) spectroscopy were used to investigate the structure of the purified A. auricular polysaccharide (AAP‐I) and revealed that it is α‐glycosidically linked. After 14 and 28 days of AAP‐I orally administered, the AAP‐I significantly decreased the levels of total cholesterol, triglyceride, and low‐density lipoprotein cholesterol in mice in which hyperlipidemia had been induced by a high fat diet ( P < 0.05). The results revealed that AAP‐I from SSF of A. auricular mycelium possesses potent hypolipidemic properties. The polysaccharide may be useful as a functional food additive and a hypolipidemic agent.